Lebanese cancer patients - Doumit, Myrna Abi Abdallah (2008)
The purpose of this study was to describe and interpret the phenomenon of communication as lived by Lebanese cancer patients. Phenomenology based on the Utrecht School was chosen as an interpretive descriptive methodology to guide the processes of data collection, analysis and synthesis. In-depth semi structured interviews were carried out with a purposeful sample of ten cancer patients. Results of this qualitative study emphasise the needs of Lebanese cancer patients for a clear and truthful communication with healthcare professionals, and family members. Informants highlighted the influence of words used during communication on their outlook and morale. They also stressed the need to move from the paternalistic approach in care provision to patient-centered care that promotes patient autonomy. Informants clearly accentuated their rights to be told the truth about their condition.